Do pancreatic cancer and chronic pancreatitis share the same genetic risk factors? A PANcreatic Disease ReseArch (PANDoRA) consortium investigation. Issue 2 (16th October 2017) - Campa, Daniele; Pastore, Manuela; Capurso, Gabriele; Hackert, Thilo; Di Leo, Milena; Izbicki, Jakob R.; Khaw, Kay‐Tee; Gioffreda, Domenica; Kupcinskas, Juozas; Pasquali, Claudio; Macinga, Peter; Kaaks, Rudolf; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is a very aggressive tumor with a five‐year survival of less than 6%. Chronic pancreatitis (CP), an inflammatory process in of the pancreas, is a strong risk factor for PDAC. Several genetic polymorphisms have been discovered as susceptibility loci for both CP and PDAC. Since CP and PDAC share a consistent number of epidemiologic risk factors, the aim of this study was to investigate whether specific CP risk loci also contribute to PDAC susceptibility. We selected five common SNPs (rs11988997, rs379742, rs10273639, rs2995271 and rs12688220) that were identified as susceptibility markers for CP and analyzed them in 2, 914 PDAC cases, 356 CP cases and 5, 596 controls retrospectively collected in the context of the international PANDoRA consortium. We found a weak association between the minor allele of the PRSS1‐PRSS2‐ rs10273639 and an increased risk of developing PDAC (ORhomozygous = 1.19, 95% CI 1.02–1.38, p = 0.023). Additionally all the SNPs confirmed statistically significant associations with risk of developing CP, the strongest being PRSS1‐PRSS2‐ rs10273639 (ORheterozygous = 0.51, 95% CI 0.39–0.67, p = 1.10 × 10 −6 ) and MORC4‐rs 12837024 (ORhomozygous = 2.07 (1.55–2.77, p trend = 0.7 × 10 −11 ). Taken together, the results from our study do not support variants rs11988997, rs379742, rs10273639, rs2995271 and rs12688220 as strong predictors of PDAC risk, but further support the role of these SNPs in CP susceptibility. Our study suggests that CP and PDAC probably do not share genetic susceptibility, at least in terms of high frequency variants. Abstract : What's new? Do pancreatic cancer and chronic pancreatitis share common genetic risk factors? Probably not, according to new results. Because chronic pancreatitis is a risk factor for pancreatic ductal adenocarcinoma, these authors wondered whether the same genetic loci paved the way for both conditions. Using genotypes from almost 3, 000 cancer patients, they investigated five common polymorphisms associated with chronic pancreatitis risk. They found that none of them strongly predicted pancreatic cancer.